The reduction methods of operator's radiation dose for portable dental X-ray machines - Jeong-Yeon Cho; Won-Jeong Han (Korean Academy of Conservative Dentistry, 2012)
Objectives This study was aimed to investigate the methods to reduce operator's radiation dose when taking intraoral radiographs with portable dental X-ray machines. Materials and Methods Two kinds of portable dental X-ray machines (DX3000, Dexcowin and Rextar, Posdion) were used. Operator's radiation dose was measured with an 1,800 cc ionization chamber (RadCal Corp.) at the hand level of X-ray tubehead and at the operator's chest and waist levels with and without the backscatter shield. The operator's radiation dose at the hand level was measured with and without lead gloves and with long and short cones. Results The backscatter shield reduced operator's radiation dose at the hand level of X-ray tubehead to 23 - 32%, the lead gloves to 26 - 31%, and long cone to 48 - 52%. And the backscatter shield reduced operator's radiation dose at the operator's chest and waist levels to 0.1 - 37%. Conclusions When portable dental X-ray systems are used, it is recommended to select X-ray machine attached with a backscatter shield and a long cone and to wear the lead gloves.